Load transfer-crack width relation of non-dowelled jointed plain concrete short slabs - Pradena, Mauricio; Houben, Lambert (The Baltic Journal of Road and Bridge Engineering, 2018)
Non-dowelled short slabs are a cost-effective innovation of jointed plain concrete pavements. The development of this innovation has been concentrated in their structural performance. Still there is a lack of specific studies of the relation load transfer – crack width, being the crack width at joint the direct cause of the aggregate interlock. Considering that their provision of load transfer relies on aggregate interlock, the objective of the present article is to develop the relationship between the load transfer by aggregate interlock and its direct cause (the crack width) specifically for innovative non-dowelled short concrete slabs pavements. For that, the analysis includes a validated nonlinear aggregate interlock model incorporated in a 3D Finite Element program, laboratory results, and field measurements performed as part of the present investigation. The results show that due to the small crack widths, the short slabs are able to provide adequate load transfer (not less than 70%) even without dowels bars. Indeed, in this case, the load transfer relies on aggregate interlock and the results of the Faultimeter (residual value more than 0) have confirmed this interlocking for crack widths at joints not more than 1.2 mm, which are typical values in short slabs when the joints are activated. For that, the Early Entry saw cutting method needs to be modified or applied as a complementary method to perform the joints. Although in short concrete slabs pavements the provision of load transfer is already guaranteed by the small crack widths at joints, the application of high-quality coarse aggregates provides even higher load transfer.